The Effect of Spiritual Therapy on Hope and Self-efficacy of Hemodialysis Patients - Fatemeh Noghani; Peiman Fereidouni Sarijeh; Hamid Sahrif Nia (Mashhad University of Medical Sciences, 2024)
Background: The problems such as depression, anxiety, hopelessness, stress and suicide in hemodialysis patients shows the need to support these patients to increase adaptation to the disease. Spiritual therapy introduces the person to the search for meaning, purpose, meaning in life, and the important beliefs and values.Aim: The present study was conducted with aim to determine the effect of spiritual therapy on hope and self-efficacy of hemodialysis patients.Method: This quasi-experimental study was performed in 2020 on 100 patients undergoing hemodialysis in Amol, Iran. The subjects were randomly divided into case (n=50) and control (n=50) groups. The intervention was performed in case group as 9 training sessions during 5 weeks based on spiritual therapy. Snyder's Hope and Scherer general self-efficacy standard questionnaires were used to collect data. Data were analyzed by SPSS (version 18) and paired t-test, analysis of covariance and independent t-test. p<0.05 was considered statistically significant.Results: The mean scores of self-efficacy and hope showed a statistically significant difference before and after spiritual therapy in the case group (p=0.011, p=0.006, respectively). Also, the difference between the mean score of patients' hope in the case and control groups was statistically significant after the intervention (p=0.006). Also, there was a significant difference between the case and control groups regarding self-efficacy after the intervention (p=0.011).Implications for Practice: Spiritual intervention can be done as an effective and cost-effective method in hemodialysis patients to increase the hope and self-efficacy of these patients.